Intraperitoneal infection of A/J and CD1 mice with coxsackievirus B2 and its mutants - Maria Borsanyiova; Katarina Berakova; Brigita Benkoova; Michaela Pellerova; A. Michael Lindberg; Shubhada Bopegamage (Acta Virologica)
Coxsackieviruses (CVs) belong to the genus Enterovirus and family Picornaviridae. Mutants can arise within the replication cycle of RNA viruses. The prototype CVB2 Ohio-1 (CVB2/O) strain adapted to rhabdomyosarcoma (RD) cells induced cytolytic infection and showed three-point mutations in the genome (CVB2/O/RD). The aim of this experimental study was to compare the effect of one or multiple viral mutations in viral protein 1 (VP1) or region 2C of CVB2/O on pathogenesis in two different mouse models. Male A/J and CD1 (10–12 g) mice were infected intraperitoneally with CVB2/O and its mutants or mock infected (control mice). Mice were sacrificed on days 0, 5, 7, 10, and 55 post infection. Blood, heart, and pancreas were collected for virological and histopathological analysis. The presence of viral RNA in the heart and pancreas of infected mice was studied. Different cytokines were detected in the serum. Pathological changes were absent in the hearts of infected mice. Maximum pathological changes were identified in the pancreas of infected A/J mice. Infiltration of pancreatic cells was observed depending on the mouse strain and mutants. CD1 mice were less susceptible to CVB2 infection. CVB2/O/VP1-Q164K mutant induced maximum changes in the pancreas of A/J-infected mice. We suggest that the single altered amino acid in the VP1 protein was related to the virulence factor and was associated with the pathology and presence of viral RNA in the pancreas of infected A/J mice.